A novel hierarchically porous magnetic carbon derived from biomass for strong lightweight microwave absorption. (February 2019) - Zhao, Huanqin; Cheng, Yan; Lv, Hualiang; Ji, Guangbin; Du, Youwei
Abstract: Recent findings reveal that biomass material sometimes exhibits novel microstructure, in particular for some heterostructures and microtubular channels, which is hard to be realized by conventional chemical synthesis. Utilizing of intrinsic microstructure characteristic of biomass in nature to optimize microstructure and material component is regarded as a potential way to deal with ever-growing electromagnetic (EM) interference issue. This research taking rice as an example, a pre-treatment is conducted by dipping and annealing to obtain porous carbon and simultaneously incorporation of beneficial magnetic component. By optimizing of microstructure and material component, the fabricated hierarchically porous magnetic carbon (HPMC) material shows excellent EM wave performance with minimum reflection loss (RLmin ) of −52 dB and wide effective absorption bandwidth (EAB) of 5 GHz at low filler content of 15 wt%. This work paves the way for development of biomass as a low-cost, green and renewable high-performance carbon-based absorber. Graphical abstract: Image 1